Penyuluhan Kesehatan : Edukasi Gizi Seimbang pada Remaja Putri di SMP Negeri 2 Bunta, Kabupaten Banggai, Provinsi Sulawesi Tengah - Mariyati Mariyati; Zamli, Zamli (Lembaga Pengembangan Kinerja Dosen, 2025)
The number of school-age adolescent girls in Banggai Regency, Central Sulawesi, still faces serious challenges related to nutritional problems such as anemia and chronic energy deficiency (SEZ). Low nutritional literacy and unbalanced food consumption habits also worsen their nutritional status, especially during puberty when nutritional needs increase significantly. This service activity aims to increase the understanding and awareness of young women on the principles of balanced nutrition through a participatory educational approach. The implementation of the activity was carried out at SMP Negeri 2 Bunta, Simpang Raya District, involving 30 students in grades VII and VIII as well as UKS supervisory teachers. The intervention included providing material on